Psychological distress in mid-life: evidence from the 1958 and 1970 British birth cohorts. Issue 2 (13th October 2016) - Ploubidis, G. B.; Sullivan, A.; Brown, M.; Goodman, A.
Abstract : Background: This paper addresses the levels of psychological distress experienced at age 42 years by men and women born in 1958 and 1970. Comparing these cohorts born 12 years apart, we ask whether psychological distress has increased, and, if so, whether this increase can be explained by differences in their childhood conditions. Method: Data were utilized from two well-known population-based birth cohorts, the National Child Development Study and the 1970 British Cohort Study. Latent variable models and causal mediation methods were employed. Results: After establishing the measurement equivalence of psychological distress in the two cohorts we found that men and women born in 1970 reported higher levels of psychological distress compared with those born in 1958. These differences were more pronounced in men ( b = 0.314, 95% confidence interval 0.252–0.375), with the magnitude of the effect being twice as strong compared with women ( b = 0.147, 95% confidence interval 0.076–0.218). The effect of all hypothesized early-life mediators in explaining these differences was modest. Conclusions: Our findings have implications for public health policy, indicating a higher average level of psychological distress among a cohort born in 1970 compared with a generation born 12 years earlier. Due to increases in life expectancy, more recently born cohorts are expected to live longer, which implies – if such differences persist – that they are likely to spend more years with mental health-related morbidity compared with earlier-born cohorts.